Hypertension-associated mitochondrial DNA 4401A>G mutation caused the aberrant processing of tRNAMet, all 8 tRNAs and ND6 mRNA in the light-strand transcript. Issue 19 (28th August 2019) - Zhao, Xiaoxu; Cui, Limei; Xiao, Yun; Mao, Qin; Aishanjiang, Maerhaba; Kong, Wanzhong; Liu, Yuqi; Chen, Hong; Hong, Fang; Jia, Zidong; Wang, Meng; Jiang, Pingping; et al.
Abstract: Mitochondrial tRNA processing defects were associated with human diseases but their pathophysiology remains elusively. The hypertension-associated m.4401A>G mutation resided at a spacer between mitochondrial tRNA Met and tRNA Gln genes. An in vitro processing experiment revealed that the m.4401A>G mutation caused 59% and 69% decreases in the 5′ end processing efficiency of tRNA Gln and tRNA Met precursors, catalyzed by RNase P, respectively. Using human umbilical vein endothelial cells-derived cybrids, we demonstrated that the m.4401A>G mutation caused the decreases of all 8 tRNAs and ND6 and increases of longer and uncleaved precursors from the Light-strand transcript. Conversely, the m.4401A>G mutation yielded the reduced levels of tRNA Met level but did not change the levels of other 13 tRNAs, 12 mRNAs including ND1, 12S rRNA and 16S rRNA from the Heavy-strand transcript. These implicated the asymmetrical processing mechanisms of H-strand and L-strand polycistronic transcripts. The tRNA processing defects play the determined roles in the impairing mitochondrial translation, respiratory deficiency, diminishing membrane potential, increasing production of reactive oxygen species and altering autophagy. Furthermore, the m.4401A>G mutation altered the angiogenesis, evidenced by aberrant wound regeneration and weaken tube formation in mutant cybrids. Our findings provide new insights into the pathophysiology of hypertension arising from mitochondrial tRNA processing defects.